Embedding Sustainability across a Teacher Education Course: Teacher Educator Experiences - Kim Beasy; Stephanie Richey; Jillian Brandsema; Vinh To (Australian Journal of Environmental Education)
Education for Sustainable Development (ESD) remains an urgent priority to combat the numerous social, environmental and political crises prominent in the 21st century. This article shares the experiences of teacher educators who integrated ESD into discipline-specific units of study for pre-service teachers. Using a collaborative auto-ethnographic approach, we explore how curriculum change for ESD was navigated and discuss how institutional support was essential for providing legitimacy and necessary resources. Drawing on Noddings’ approach to ethics of care, we emphasise the significance of valuing the perspectives and experiences of stakeholders involved in curriculum change and advocate for inclusive and responsive approaches that engage individuals meaningfully throughout the process.